Rancangan Sistem Informasi Perpustakaan Berbasis Website Menggunakan Barcode Di Sekolah MA Raden Rahmat - Khofifatul Wakhidah; Budiman Budiman; Winarti Winarti (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Internal libraries are usually for example bookstores, where books, research results and journals are neatly stored. So that people who read it have to go to the library and look for the desired book. Many sources of scientific information, books, documents, library facilities, can be disseminated according to certain systems. . Methodology is doing something to achieve a goal. The framework describes the stages of conducting research. Because it helps researchers to explain the work steps that will be carried out in solving the problem. Based on the waterfall model, a discussion of each can be described, such as Analysis. Author's Design, Testing, Support or maintenance After Realizing the system design At this stage, the author implements the design results obtained previously. before the system is actually used properly by the user, the system requires a test phase first to ensure there are no problems in using the PHP programming language and the MySQL database is used as a programming language. The design of this barcode-based library information system is used to make it easier for librarians and members to borrow library books in managing library data. Based on the discussion and conclusions presented, a development proposal for further research.